Architecture and Naturing Affairs. Media and Architectonic Concepts (2020)
Technology, the authors investigate in what multifaceted way architecture in this anthology with contributions about architecture, media, and infrastructure and information is in tune with contemporary technology, and in what way we live with them. The book is divided into following parts: breeding (medialising matter), breathing (transcending language), and inhabiting (making things inhabitable). The compilation of various text contributions creates a lexicon of ‘naturing affairs’ and is written for readers who look for an inspiring overview of our medialised environments.